The effects of mode of delivery, maternal age, birth weight, gender and family history on screening hearing results: A cross sectional study. (April 2021) - Al-Balas, Hasan Ibrahim; Nuseir, Amjad; Zaitoun, Maha; Al-Balas, Mahmoud; Khamees, Almu'atasim; Al-Balas, Hamzeh
Abstract: Introduction: Congenital hearing impairment is one of the principal issues that make distress to families especially those with a family history of hearing problems. Early detection of hearing impairment can make a difference regarding cognitive, attention, learning, speech, and social and emotional development of babies. Otoacoustic test emission is a very common screening test that can be used to pick up early cases and relieve family stress. We tried to evaluate the factors that may disrupt our results regarding the OAE test. Methods: A cross-sectional study included infants who were admitted to the nursery unit alone. Infants who were admitted to the NICU unit, infants with craniofacial anomalies, infants with vernix in the external auditory canal, and Infants with Stigmata associated with a syndrome known to include a sensorineural hearing loss were excluded from the study. Both transient evoked otoacoustic emissions (TEOAE) with distortion product otoacoustic emissions (DPOAE) Screening tests were performed by the same professional audiologist experienced in neonatal screening. Results: A total of 1413 newborns (733 males and 680 females) were included in the study. Among them, 1368 babies (96.8%) passed the first OAE in both ears, while 45 babies (3.2%) didn't pass the first OAE in one or both ears.Significant correlations between the female gender and family history of congenital hearing loss with failure of the first OAE test results. Moreover, vaginal delivery (VD) infants had a 1.5-fold higher failure rates of first OAE test screening results in comparison to caesarian delivery (CD) infants. Conclusion: Our study demonstrated higher failure rates of the first OAE in female infants, vaginal delivery infants, and infants with a family history of hearing impairment. It is recommended to postpone the first phase of hearing screening for those infants until the first scheduled vaccine appointment to achieve higher compliance attendance, and decrease family stress associated with false-negative results of the test. Highlights: Hearing impairment is a stressful condition that disturbs family quality of life. Early detection of hearing impairment can make a difference in child development. Otoacoustic test emission is a screening test with considerable reliability. Early Otoacoustic test can have false negative results in specific condition. Postpone the first phase of hearing screening decrease the family stress.